ISSUES OF LIABILITY FOR CRIMES IN THE FORM OF TORTURE UNDER AGGRAVATING CIRCUMSTANCES, AS WELL AS TAKING INTO ACCOUNT THE POSITION OF THE VICTIM IN THE CRIMINAL LEGISLATION OF THE CIS COUNTRIES - Saparovna , Niyozova Salomat (PT. Antis International Publisher, 2024)
The issues of responsibility for crimes in the form of torture under aggravating circumstances, as well as taking into account the position of the victim in the criminal legislation of the CIS countries are discussed. During the analysis of the article, the issues of criminal liability for crimes in the form of torture in the criminal legislation of the Republic of Uzbekistan and certain developed foreign countries, the CIS countries in the aspect of the legal status of the victim, the prevention of victimhood of these crimes were studied, and proposals were developed regarding the improvement of some legislative acts and amendments and additions to the criminal legislation.